The (r)evolution and decolonization of social work ethics: The Global Social Work Statement of Ethical Principles. (November 2019) - Sewpaul, Vishanthie; Henrickson, Mark
The approval of the 2014 joint Global Definition of Social Work required that international social work associations review the associated ethical principles of social work. The Global Social Work Statement of Ethical Principles ( GSWSEP ) was approved by international social work bodies in Dublin in July 2018. While the previous Statement of Ethics emphasized liberal humanist values common in the European–North American axis, the GSWSEP recognizes the global nature of the social work profession and locates human dignity at the core of social work ethics. The GSWSEP problematizes the core principles of social work, and responds to calls to decolonize social work in the context of the increasing regulation of social work.